FEMINISME EKSISTENSIAL SIMONE DE BEAUVOIR: PERJUANGAN PEREMPUAN DI RANAH DOMESTIK - Mutiara Prameswari, Ni Putu Laksmi; Nugroho, Wahyu Budi; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI: SOROT, 2019)
ABSTRACT   The results of existential feminism insight of Simone de Beauvoir in the sociological framework study include into the character of social definition paradigm. Different from other feminism view which more struggling the women’s insights in public arena, the existential feminism exists for struggling women in the domestic arena. The domestic arena in this case is women as housewives and workplace. The struggle of women in the domestic arena is the form of countering in direct way and face-to-face when women are threatened by men. Even, women possess a freedom to break values, norms, and the construction from the society who shackles them. On the other hands, women also possess free choices to make themselves be any roles, because in existentialism human is freedom itself so are the women. Keywords: Existential feminism, Simone de Beauvoir, women struggle, domestic arena.